Data driven mathematical modeling reveals the dynamic mechanism of MSC‐induced neovascularization. Issue 3 (5th December 2018) - Yu, Yingting; Situ, Qiaojun; Jia, Wangyue; Li, Junxiang; Wu, Qiong; Lei, Jinzhi
ABSTRACT: Coculture of mesenchymal stem cells (MSCs) and vascular endothelial cells (ECs) in vitro leads to the formation of a capillary‐like reticular structure by ECs, which has great potential as a better substitute for artificial blood vessels in terms of stability and functionality. To investigate the mechanisms of the early neovascularization induced by MSCs, we analyzed the kinematic features of the motion of ECs and concluded that the dynamic interaction between cells and the extracellular matrix would reveal the capillary‐like structure formation. Based on this hypothesis, we proposed a mathematical model to simulate the vascular‐like migration pattern of ECs in silico, which was confirmed by in vitro studies. These in vitro studies validated that the dynamic secretion and degradation of collagen I is the critical factor for capillary structure formation. The model proposed based on cell tracking, single cell sequencing, and mathematical simulation provides a better understanding of the neovascularization process induced by MSCs and a possible simple explanation guiding this important cellular behavior.—Yu, Y., Situ, Q., Jia, W., Li, J., Wu, Q., Lei, J. Data driven mathematical modeling reveals the dynamic mechanism of MSC‐induced neovascularization. FASEB J. 33, 3496–3509 (2019). www.fasebj.org